Pengaruh Keuangan Hijau terhadap Profitabilitas dan Reputasi Perusahaan (The Effect of Green Finance on Profitability and Corporate Reputation) - Annisa, Eva; Luayyi, Sri; Ratih, Nur Rahmanti (STIE Malangkucecwara, 2025)
This study analyzes the effect of implementing green finance on the profitability and reputationof mining companieslisted ontheIndonesia Stock Exchangefor the period 2021-2024. The purposive sampling method is used to obtain sample criteria, the sample consists of nine mining companies. The data analyzed are secondary data derived from annualreports and corporatesustainability reports. Data analysis was carried out through descriptive statistical tests, classical assumption tests, simple linear regression, as well as testing the coefficient of determination, F test, and T test. The results showed that green finance has a significant effect on corporate profitability, but does not have a significant impact on corporate reputation